A backpacker habitus: the body and dress, embodiment and the self. Issue 3 (2nd July 2016) - O'Regan, Michael
ABSTRACT: As all cultures 'dress' the body through clothing, tattooing and other forms of body adornment such as cosmetics, dress offers a useful lens through which to explore the ways in which identities are constituted in modern leisure and tourism cultures. An analysis of the dress and embodied subjectivity of western backpackers in Nepal finds that dress is constitutive of self-identity and the ways backpackers imagine themselves. This study argues that dress remains an important aspect of a secondary socialization that, in an evolving process, leads to specific (western) backpacker habitus. The use of Pierre Bourdieu as a theoretical resource unravels the relationship between body and dress, embodiment and the self and shows how dress embellishes the body by adding an array of meanings within backpacking culture.